2022
DOI: 10.1371/journal.pone.0270658
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle changes and mental health states of women hospitalized due to COVID-19

Abstract: Purpose Many studies have evaluated the impact of the COVID-19 pandemic on women’s mental health and menstrual changes. However, most of these studies only included nonhospitalized COVID-19 patients, while information on hospitalized women is very limited. Thus, this study aimed to examine the mental health status and menstrual changes in hospitalized female COVID-19 patients. Methods A survey was administered to female COVID-19 patients in the isolation ward of a national referral hospital in Indonesia betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…Some women complained of shortened or delayed menstrual cycles, while some complained of heavier or lighter bleeding. The altered menstruation pattern following COVID-19 infection or vaccination is a very current issue, and different results are reported from different countries and races [ 5 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some women complained of shortened or delayed menstrual cycles, while some complained of heavier or lighter bleeding. The altered menstruation pattern following COVID-19 infection or vaccination is a very current issue, and different results are reported from different countries and races [ 5 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the Arizona CoVHORT study, the incidence of menstrual changes after COVID-19 infection was 16%, and in another study, it was 37.3% among hospitalized patients. In another study, the incidence of menstrual changes following infection was 47.2% [ 5 , 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, to date, the majority of COVID-19 studies [20,21] concerning the menstrual cycle have focused on patients infected by the virus, while there has been little research on menstrual health for medical staff working on the frontline of the ght against the epidemic. However, Huang and Zhao [22] found that healthcare workers were more at risk of mental health problems.…”
Section: Introductionmentioning
confidence: 99%